Assessing the distribution and habitat use of four felid species in Bukit Barisan Selatan National Park, Sumatra, Indonesia - Jennifer L. McCarthy; Hariyo T. Wibisono; Kyle P. McCarthy; Todd K. Fuller; Noviar Andayani (Global Ecology and Conservation, 2015)
There have been few targeted studies of small felids in Sumatra and there is little information on their ecology. As a result there are no specific management plans for the species on Sumatra. We examined data from a long-term camera trapping effort, and used Maximum Entropy Modeling to assess the habitat use and distribution of Sunda clouded leopards (Neofelis diardi), Asiatic golden cats (Pardofelis temminckii), leopard cats (Prionailurus bengalensis), and marbled cats (Pardofelis marmorata) in Bukit Barisan Selatan National Park. Over a period of 34,166 trap nights there were low photo rates (photo events/100 trap nights) for all species; 0.30 for golden cats, 0.15 for clouded leopards, 0.10 for marbled cats, and 0.08 for leopard cats. There is overlap in the predicted distributions of clouded leopards, golden cats, and marbled cats; indicating areas of high conservation importance for these species within the park. The predicted distribution of leopard cats was discrete from the other species which is important to consider in the development of conservation strategies. This study provides important documentation of small felid distribution in Sumatra, information for the development of management strategies within the park, and a basis upon which to develop future research for the species.